Arterial hypertension management in pregnancy - R. I. Stryuk (Российский кардиологический журнал, 2013)
Arterial hypertension (AH) in pregnancy is a heterogeneous pathology. It includes chronic AH (secondary AH and essential AH) which has been observed before pregnancy; gestational AH which develops approximately after 20 weeks of pregnancy and disappearing within 42 days after childbirth; pre-eclampsia (gestosis) which is a combination of AH and proteinuria; and unclassified AH which is diagnosed when blood pressure (BP) is first measured after 20 weeks of pregnancy, and elevated BP, with or without systemic signs and symptoms, is detected. AH in pregnancy increases the risk of complications both for the mother and the child, which points to the need for its active diagnostics and monitoring of the status of target organs and feto-placental complex. Pharmacotherapy of AH in pregnancy is based on the balance of its effectiveness and safety. Therefore, the first-choice medications are methyldopa, dihydropyridine calcium antagonists (nifedipine SR), and cardio-selective beta-blockers. AH in pregnancy is a risk factor of cardiovascular disease across life course stages in women.